2022
DOI: 10.1212/nxi.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 Antibodies Are Associated With Blood-Brain Barrier Breakdown in Anti–Myelin Oligodendrocyte Glycoprotein Antibody–Associated Disorder

Abstract: Background and ObjectivesTo analyze (1) the effect of immunoglobulin G (IgG) from patients with anti–myelin oligodendrocyte glycoprotein antibody (MOG-Ab)–associated disorder on the blood-brain barrier (BBB) endothelial cells and (2) the positivity of glucose-regulated protein 78 (GRP78) antibodies in MOG-Ab–associated disorders.MethodsIgG was purified from sera with patients with MOG-Ab–associated disorder in the acute phase (acute MOG, n = 15), in the stable stage (stable MOG, n = 14), healthy controls (HCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The mechanism by which the anti-GRP78 antibodies break the permeability of the BBB involves their binding to the scGRP78 on the brain microvascular endothelial cells (BMECs), inducing nuclear translocation of NF-κB that facilitates ICAM-1 transcription and promotes binding of activated immune cells that enhance the diameter of cerebral blood vessels in [ 58 ]. Similar mechanisms have been observed with anti-GRP78 antibodies in AMOGAD [ 56 ] and LEMS [ 8 ] that induce brain endothelial cells to open the BBB, thereby allowing access to other pathogenic antibodies in the CNS. A compromised BBB and antiendothelial cell antibodies have been found in patients with SLE [ 68 ], suggesting that csGRP78 in brain endothelial cells may also be a target of antiGRP78 antibodies in SLE [ 69 ].…”
Section: Grp78 Autoantibodies In Immune-mediated Neurological Diseasessupporting
confidence: 63%
See 2 more Smart Citations
“…The mechanism by which the anti-GRP78 antibodies break the permeability of the BBB involves their binding to the scGRP78 on the brain microvascular endothelial cells (BMECs), inducing nuclear translocation of NF-κB that facilitates ICAM-1 transcription and promotes binding of activated immune cells that enhance the diameter of cerebral blood vessels in [ 58 ]. Similar mechanisms have been observed with anti-GRP78 antibodies in AMOGAD [ 56 ] and LEMS [ 8 ] that induce brain endothelial cells to open the BBB, thereby allowing access to other pathogenic antibodies in the CNS. A compromised BBB and antiendothelial cell antibodies have been found in patients with SLE [ 68 ], suggesting that csGRP78 in brain endothelial cells may also be a target of antiGRP78 antibodies in SLE [ 69 ].…”
Section: Grp78 Autoantibodies In Immune-mediated Neurological Diseasessupporting
confidence: 63%
“…GRP78 autoantibodies have been identified in MS [ 54 ], NPSLE [ 55 ], AMOGAD [ 56 ], LEMS [ 8 ], and NMO [ 57 ]. MS is a chronic inflammatory demyelinating disease of the central nervous system (CNS), characterized by the presence of focal demyelinated plaques within the white matter [ 58 ].…”
Section: Grp78 Autoantibodies In Immune-mediated Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar as for the detection of AQP4-IgG or MOG-IgG and GFAP antibodies, the establishment of a high throughput cell-based assay that allows detection of GRP78 antibodies on the cell surface of mammalian cells will be required to understand the presence of this antibody in a large set of patients and controls. In NMOSD, the presence of GRP78 antibodies was associated with LETM phenotype [91], whereas in MOGAD the rate of GRP78 antibody positivity was higher in the acute MOGAD group compared to patients with a stable MOGAD disease [90 ▪ ].…”
Section: Toward Novel Autoantibodies In Demyelination and Astrocytopathymentioning
confidence: 90%
“…MOGAD was perceived primarily as a monophasic CNS inflammatory disease, but further observations showed that a relapsing course occur in 28–60% of patients, and in up to 83% of cases with long-term observation, especially those with persistent positive MOG-IgG status. 99,143 Some evidence of subclinical disease activity and progression has been shown to be present in some of the patients with MOGAD. 2 Patients with anti-NMDAR-EN tend to have more severe neurologic presentations, and poor long-term functional outcomes, and the mortality rate has been reported between 5% and 7%.…”
Section: Discussionmentioning
confidence: 99%